CHARACTERISTICS ANALYSIS OF DRAGON FRUIT EXTRACT SKIN BETACYANIN of Hylocereus polyrhizus AND Hylocereus undatus WITH TEST OF STABILITY ORGANOLEPTIC JELLY AS ATLAS MEDIA - Lestari, Tutut Puji (Jurnal Pendidikan Biologi Indonesia, 2016)
Dragon fruit Hylocereus polyrhizusÂ  and Hylocereus undatus are familiy of cactus, grown in Malang. The high consumption of dragon fruit, have an impact on the fruit skin buildup that simply disposed of as trash. Dragon fruit skin is known to have a source of natural red dye, which is Betacyanin. The purpose of this study was to determine the characteristics of the dragon fruit peel extract Betacyanin Hylocereus polyrhizus and Hylocereus undatus as well as the stability of the organoleptic jelly, which will be developed into a learning materials atlas for class VIII Junior High School. The study was conducted in September-October 2015. The study was conducted in three stages. This type of research phase I and II is True Experimental, and phase III is development. The results of phase I shows that various concentrations of ethanol (70% and 90%) have an effect on the characteristics of the extract Betacyanin skin dragon fruit Hylocereus polyrhizus and Hylocereus undatus, but very significant effect on skin extract dragon fruit Hylocereus undatus the treatment of N2, EI at pH 4,5. Later in the phase II study results showed that different concentrations of extracts of the best Betacyanin significantly affect the organoleptic stability of jelly. The results of phase III is the development of phase I and II studies into Atlas media for 8th grade of Â Junior High School. Â